Merkel Cell Polyomavirus Detection in a Patient with Familial Epidermodysplasia Verruciformis. Issue 4 (28th March 2013) - Kwon, Eun‐Kyung M.; Halvorson, Christian R.; Rady, Peter; Tyring, Stephen; Nguyen, Harrison P.; Kao, Grace F.; Gaspari, Anthony A.
Abstract We report a case of Merkel cell polyomavirus detection in the skin of a patient with epidermodysplasia verruciformis (EDV) and a family history remarkable for an unusual inheritance pattern for EDV.